Consultores Ad Hoc - 2013 - [T&C], Textos & Contextos (Textos & Contextos (Porto Alegre), 2013)
<span style="font-size: 16.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: Georgia-Bold; font-variant: small-caps; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">Consultores A<span style="font-size: 16.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: Georgia-BoldItalic; font-variant: small-caps; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">d Hoc - <span style="font-size: 16.0pt; font-family: "Calibri","sans-serif"; mso-fareast-font-family: Calibri; mso-bidi-font-family: Georgia-Bold; font-variant: small-caps; mso-ansi-language: PT-BR; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;">2013